Research on the Impact of Digital Inclusive Finance on the New Rural Collective Economy based on Empirical Evidence from Sichuan Province - Hua, Yijia (Transactions on Economics, Business and Management Research, 2024)
This article takes Sichuan Province as the research object and explores the impact of digital inclusive finance on the new rural collective economy. Firstly, the concept, characteristics, and development forms of digital inclusive finance and the new rural collective economy were elaborated, revealing the relationship between the two. Secondly, the current development status of digital inclusive finance in Sichuan Province was analyzed, including the current situation of rural financial services, the promotion and application of digital inclusive finance in Sichuan Province, as well as the problems and challenges faced in its development. Subsequently, the impact mechanism of digital inclusive finance on the new rural collective economy was elaborated from the aspects of financial resource allocation, rural industrial structure adjustment, improvement of farmers' income, and construction of rural credit system. Finally, in response to the impact of the development of digital inclusive finance in Sichuan Province on the new rural collective economy, policy recommendations were proposed to strengthen digital infrastructure construction and network coverage, formulate policy measures to support the development of digital inclusive finance, and enhance farmers' awareness and acceptance of digital financial services. The research results indicate that digital inclusive finance has a positive impact on the development of the new rural collective economy, providing useful reference for the development of rural economy in China.